THE ROLE OF CAMERA NAVIGATION TRAINING IN ENHANCING TEAM PERFORMANCE IN VIRTUAL REALITY LAPAROSCOPY: A LITERATURE REVIEW - Parpibaeva Dinara Ayupovna; Ergashov Nodirbek Shermuxamat ugli (European Science Publishing, 2024)
Background: Virtual reality (VR) simulation has revolutionized surgical training by providing a realistic and risk-free platform for skill development. Laparoscopic surgery presents unique challenges, including the need for effective camera navigation. This literature review explores the impact of camera navigation training on team performance in VR laparoscopy. Methods: A systematic search of PubMed, MEDLINE, and Google Scholar was conducted to identify relevant studies published between January 2010 and December 2023. Keywords such as "virtual reality laparoscopy," "camera navigation training," "team performance," and "surgical simulation" were used. Studies were included if they examined the effects of camera navigation training on team dynamics, communication, and surgical proficiency in VR laparoscopy. The selected articles were critically reviewed, and key findings were synthesized. Results: The review identified several studies demonstrating that camera navigation training significantly improves team coordination, communication, and surgical proficiency. Trained teams showed better synchronization, clearer communication, and more efficient surgical maneuvers. These improvements were associated with reduced procedure times, fewer complications, and enhanced surgical outcomes. Discussion: The findings underscore the importance of integrating camera navigation training into surgical simulation curricula. Such training enhances team dynamics and surgical performance, contributing to safer and more effective laparoscopic procedures. However, further research is needed to explore the long-term effects of camera navigation training and its transferability to real-world surgeries. Conclusion: Camera navigation training is crucial for improving laparoscopic surgery outcomes. By enhancing teamwork, communication, and technical skills, such training programs prepare surgical teams for the demands of modern surgery, ultimately leading to higher standards of patient care.
Keywords: Virtual reality laparoscopy, camera navigation training, team performance, surgical simulation, laparoscopic surgery, surgical education, team coordination, communication skills, surgical proficiency.